2007
DOI: 10.1111/j.1399-6576.2007.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

The beta‐adrenoceptor antagonist propranolol counteracts anti‐inflammatory effects of isoflurane in rat endotoxemia

Abstract: Our results indicate for the first time, that blockade of beta-adrenoceptors counteracts the anti-inflammatory effects of isoflurane in endotoxemic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The only theoretical limitation we see with the intranasal challenge is that it requires light isoflurane anaesthesia. It has been suggested that isoflurane may have an anti-inflammatory effect [22,23]. However, the duration of the isoflurane anaesthesia was very short in our protocol.…”
Section: Discussionmentioning
confidence: 60%
“…The only theoretical limitation we see with the intranasal challenge is that it requires light isoflurane anaesthesia. It has been suggested that isoflurane may have an anti-inflammatory effect [22,23]. However, the duration of the isoflurane anaesthesia was very short in our protocol.…”
Section: Discussionmentioning
confidence: 60%
“…Isofl urane decreases the phagocytotic capacity of human alveolar macrophages during surgery [55]. An in vivo study using rat endotoxemia showed that the inhalation of isofl urane reduced the release of the proinfl ammatory cytokine, IL-1β in bronchoalveolar lavage fl uid (BALF) [56]. This fi nding suggests an inhibitory effect of isofl urane on proinfl ammatory cytokine release from alveolar macrophages, because the main source cells of proinfl ammatory cytokines in BALF in endotoxemia are alveolar macrophages.…”
Section: Monocyte and Macrophage Functionsmentioning
confidence: 95%
“…In humans, isoflurane may decrease phagocytic activity of human alveolar macrophages during surgery (21). In endotoxemic rats, isoflurane also inhibits the release from macrophages of TNF-a in plasma, and IL-I~both in plasma and bronchoalveolar lavage fluid (BALF) (22), an effect which seems to be counteracted from propranolol.…”
Section: Volatile Anestheticsmentioning
confidence: 99%